RANCANG BANGUN APLIKASI MONITORING HASIL PELATIHAN TENAGA KERJA DI DINAS TENAGA KERJA DAN TRANSMIGRASI (DISNAKERTRANS) KABUPATEN SUMBAWA BERBASIS ANDROID - Karisma, Yana; Esabella, Shinta (Jurnal TAMBORA, 2020)
This research was conducted with the aim to design and build an Monitoring Application for Manpower Training Results in the Android Based Manpower and Transmigration Office of the Sumbawa Regency (DISNAKERTRANS). The above program is intended so that DISNAKERTRANS can know and evaluate the quality of the training that has been carried out and know the quality of further training. The data collection method in this research is literature study and interview, while for the software development method the researcher uses the waterfall method. This application will be built in hybrid form by utilizing a smartphone as a user device and the database of this application uses MySql. The application testing method of the study is black box. This application is useful for the DISNAKERTRANS Sumbawa district to monitor the results of workforce training and find out the level of success in the process of implementing workforce training.